VÂLCAN GORGE - A BRIDGE BETWEEN THE CARPATHIAN PROVINCES - MIRCEA BARON; OANA DOBRE-BARON (Annals of the University of Petrosani: Economics)
Situated in the Southern Carpathians of Romania, Vâlcan Gorge was, from the Antiquity to the end of the XIX-th century, the main connection between southern Transylvania/Haţeg County and northern Oltenia/Gorj area. Under the circumstances, the area situated at the source of the Jiu Rivers, generically named the Jiu Valley and crossed by the road coming from Crivadia and going up in Vâlcan Gorge, sometimes benefited from being a transit area for those who traveled from one side of the Southern Carpathians to the other, but it was also always in the way of invasions that lasted up to the beginning of the modern age. Today, this road seems to regain the attention of local authorities as a possible touristic route, losing its initial role at the end of the XIX-th century when, on September 4, 1894, the present road through Jiu Gorge was inaugurated.